Application Of The Project Based Learning Model To Improve The Character Of The Student Profile Pancasila For Grade III Students In Elementary School - Trisna Jumriati; Supriadi Supriadi; Erwin Nurdiansyah (ALENA : Journal of Elementary Education, 2026)
This study aims to find out the overview of the implementation of the Project Based Learning model in grade III students of SDN Baddoka and to find out the improvement in the character of Pancasila student profiles after the application of the Project Based Learning model in grade III students of SDN Baddoka. The type and design of the research used in this study is Classroom Action Research (PTK). This research was carried out at SDN Baddoka this research, the subject of the research was grade III students of SDN Baddoka. The data analysis technique used is qualitative descriptive data analysis, namely by simplifying data, exposing or presenting data and drawing conclusions. The results of the study show that: 1). The implementation of the Project Based Learning model in grade III students of SDN Baddoka was successfully implemented using five stages of learning, namely opening (determining basic questions, design (preparing project planning), monitoring students and project progress as well as assessing results and evaluating the implementation of the PjBL: 2). With the implementation of the Project Based Learning model in grade III students of SDN Baddoka there was an increase in profile character Pancasila students in the observed dimension, namely the character of working together in the student element have the ability to collaborate with other individuals/groups (collaboration) and the student element is able to complete the tasks given to him and appreciate the efforts that have been made by other members in his group (positive interdependence) obtained the highest percentage, namely 96.30% with the Very High category, while in the student element is able to communicate,  The percentage of hearing and listening to other people's messages and ideas (communication) is 85.40% (Very High). Likewise, in the Creative dimension, the percentage of students' character is also in the Very High category, which is 88.89%